2005
DOI: 10.1093/ndt/gfi023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radio contrast media on residual renal function in peritoneal dialysis patients—a prospective study

Abstract: Administration of iopromide did not lead to a persistent decline of residual renal function in CAPD patients. Nevertheless, non-ionic hypo-osmolar CM should be given to these patients with the lowest possible dose and only if there is a real clinical indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…Although some studies have found no change in RRF after radiocontrast dye (29,30), contrast should be avoided to the extent possible. If PD patients must undergo a radiocontrast study, they should be well hydrated (although, obviously not excessively so) and the lowest volume of an iso-osmotic or low-osmotic contrast agent should be used.…”
Section: Other Factorsmentioning
confidence: 95%
“…Although some studies have found no change in RRF after radiocontrast dye (29,30), contrast should be avoided to the extent possible. If PD patients must undergo a radiocontrast study, they should be well hydrated (although, obviously not excessively so) and the lowest volume of an iso-osmotic or low-osmotic contrast agent should be used.…”
Section: Other Factorsmentioning
confidence: 95%
“…It has been reported that the use of approximately 100 mL dose of contrast media did not decrease residual kidney function in patients undergoing peritoneal dialysis with a creatinine clearance (CCr) of 4.4-7.0 mL/min/1.73 m 2 compared with the control group [46,47]. Urine volume had a range of 1,300-1,800 mL/ day in many patients enrolled in these studies.…”
Section: Level Of Evidence: Iva Grade Of Recommendation: Not Applicablementioning
confidence: 96%
“…2 ml/min/1.73 m 2 , both occurring within two 3-monthly measurements and persistent thereafter. These cut-off values were chosen by consensus applying the Delphi technique on clinical relevance and the basis of data from previous studies [3,4,9,10,18,20] . The Delphi technique is a structured, written consensus process whereby documents are anonymously circulated within an expert group, with each round of the document incorporating the feedback from the previous round until consensus has been achieved.…”
Section: Definitions Of Rrf Decline and Variablesmentioning
confidence: 99%
“…neutral, bicarbonate-buffered dialysis solutions with low levels of glucose degradation products [13,14] , prevention of peritonitis, and avoiding the use of nephrotoxic drugs and radiocontrast media [15][16][17][18] , although the effects of these protective strategies to preserve RRF are not undisputed [18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
See 1 more Smart Citation